Transcription Factor Control of Lymphatic Quiescence and Maturation of Lymphatic Neovessels in Development and Physiology - Tabrizi, Zarah B.; Ahmed, Nada S.; Horder, Joseph L.; Storr, Sarah J.; Benest, Andrew V. (Frontiers in Physiology, 2021)
The lymphatic system is a vascular system comprising modified lymphatic endothelial cells, lymph nodes and other lymphoid organs. The system has diverse, but critical functions in both physiology and pathology, and forms an interface between the blood vascular and immune system. It is increasingly evident that remodelling of the lymphatic system occurs alongside remodelling of the blood microvascular system, which is now considered a hallmark of most pathological conditions as well as being critical for normal development. Much attention has focussed on how the blood endothelium undergoes phenotypic switching in development and disease, resulting in over two decades of research to probe the mechanisms underlying the resulting heterogeneity. The lymphatic system has received less attention, and consequently there are fewer descriptions of functional and molecular heterogeneity, but differential transcription factor activity is likely an important control mechanism. Here we introduce and discuss significant transcription factors of relevance to coordinating cellular responses during lymphatic remodelling as the lymphatic endothelium dynamically changes from quiescence to actively remodelling.